2013
DOI: 10.1111/hiv.12099
|View full text |Cite
|
Sign up to set email alerts
|

Expanded HIV testing in high‐prevalence areas in England: results of a 2012 audit of sexual health commissioners

Abstract: The aim of the study was to examine whether UK HIV testing guidelines which recommend the expansion of HIV testing in high HIV prevalence areas have been implemented in England. MethodsAn online survey tool was used to conduct an audit of sexual health commissioners in 40 high HIV prevalence areas (diagnosed prevalence > 2 per 1000) between May and June 2012. Responders were asked to provide details of expanded HIV testing programmes that they had commissioned in nontraditional settings and perceived barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In addition, late diagnosis of HIV infection has been selected as a key indicator of Public Health Outcome Framework in England since 2010 [21]. Despite these recommendations, there is little evidence to date of local initiatives to expand HIV testing beyond STI clinics [22] and an estimated 8,000-9,000 men remain undiagnosed annually across the UK [8]. The numbers undiagnosed has remained stable throughout the decade and modelling suggests that the large majority of transmissions come from men unaware of their infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, late diagnosis of HIV infection has been selected as a key indicator of Public Health Outcome Framework in England since 2010 [21]. Despite these recommendations, there is little evidence to date of local initiatives to expand HIV testing beyond STI clinics [22] and an estimated 8,000-9,000 men remain undiagnosed annually across the UK [8]. The numbers undiagnosed has remained stable throughout the decade and modelling suggests that the large majority of transmissions come from men unaware of their infection [23].…”
Section: Discussionmentioning
confidence: 99%
“…The UK NICE guideline also builds on prioritising high-transmission geographies, by recommending more ‘routine HIV testing’ in high-prevalence areas, for example, in newly registered patients and during routine laboratory blood tests 12 13. In the UK, however, the concept of ‘routine HIV testing’ in high-prevalence areas is not well implemented 26 27. Our data indicate opportunities for routine testing in this particular area of Amsterdam, which qualifies as a high-prevalence area: in 39.2% of HIV cases, one or more laboratory blood tests were performed 1 year prior to diagnosis.…”
Section: Discussionmentioning
confidence: 81%
“…However, studies and reviews have shown there is a general lack of awareness and knowledge of the 2008 guidelines by HCPs [72][73][74]. Previous reviews and audits [75,76] show that adherence and application of these guidelines is poor, during the eight years after their publication, mainly due to limited test offer and lack of knowledge of HIV ICs by the HCP [75,[77][78][79].…”
Section: Discussionmentioning
confidence: 99%